2018
DOI: 10.3390/ijms19102958
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Macrophage Activation and Polarization by HCC-Derived Exosomal lncRNA TUC339

Abstract: Exosomes released by cells can serve as vehicles for delivery of biological materials and signals. Long non-coding RNAs (lncRNAs) are non-coding RNAs longer than 200 nt, which roles are increasingly appreciated in various biological content. Tumor-derived exosomal lncRNAs have been implicated as signaling mediators to orchestrate cell function among neighbor tumor cells. However, the role of tumor-derived lncRNAs in cross-talk with environmental macrophages has yet to be explored. In this paper, we demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
176
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(179 citation statements)
references
References 31 publications
3
176
0
Order By: Relevance
“…Exosomes are small membrane-bound vesicles that deliver a specific cargo of proteins and nucleic acids from the parent cells to the recipient cells. Several studies indicate that exosome-transmitted lncRNAs secreted from tumor cells can promote the immunosuppressive function of stromal cells, such as cancer associated fibroblasts and macrophages (37)(38)(39). Additionally, the phenomena that exosomes being delivered from immune cells to tumor cells or other kinds of immune cells are observed.…”
Section: Features and Functional Modules Of Lncrnas In Tumor Immune Rmentioning
confidence: 99%
See 2 more Smart Citations
“…Exosomes are small membrane-bound vesicles that deliver a specific cargo of proteins and nucleic acids from the parent cells to the recipient cells. Several studies indicate that exosome-transmitted lncRNAs secreted from tumor cells can promote the immunosuppressive function of stromal cells, such as cancer associated fibroblasts and macrophages (37)(38)(39). Additionally, the phenomena that exosomes being delivered from immune cells to tumor cells or other kinds of immune cells are observed.…”
Section: Features and Functional Modules Of Lncrnas In Tumor Immune Rmentioning
confidence: 99%
“…Tumor-derived exosomal lncRNAs have been indicated as signaling mediators that orchestrate the communications between tumor cells and macrophages in TME. Li et al demonstrated that hepatocellular carcinoma (HCC) cell-derived exosomes contained overexpressed TUC339 lncRNA, which may be taken up by the non-polarized THP-1 macrophages (37). Additionally, in vitro experiments suggested that TUC339 is majorly involved in macrophage polarization (37).…”
Section: Effect Of Lncrna On Immune Cells Within Tmementioning
confidence: 99%
See 1 more Smart Citation
“…As we have mentioned, the deregulation and dysfunction of lncRNAs in the process of a proinflammatory (M1) to an anti-inflammatory phenotype (M2) have been observed [38,53]. In the present study, we attempted to identify lncRNAs related to the inappropriate activation of macrophage phenotypes (macrophage polarization) after SCI.…”
Section: Selection Of Lncrnas and Genes Related To Macrophage Polarizmentioning
confidence: 90%
“…LncRNA TUC339 is enriched in HCC‐derived exosomes, regulating the M2 polarization of macrophages and reducing the phagocytic function of macrophages after their uptake by THP‐1 cells. Therefore, intercellular delivery of TUC339 by exosomes is one of the signaling mechanisms that promote the HCC growth . LncRNA H19 is enriched in CD90 + HCC cells and can be transferred by exosomes to ECs to stimulate endothelial angiogenesis by regulating the expression of vascular endothelial growth factor (VEGF) receptor 1 and VEGF.…”
Section: Introductionmentioning
confidence: 99%